ANALISIS CAKUPAN AREA JARINGAN LONG TERM EVOLUTION (LTE/4G) DI WILAYAH MAKASSAR. - Rahmania Rahmania (VERTEX ELEKTRO, 2020)
Long Term Evolution (LTE) refers to state of the art of technology in mobile telecommunication. It has an uplink capacity up to 50 megabits per second (Mbps), and 100 Mbps of the downlink. The purpose of this study is to provide information on the development of LTE in Makassar, and provide information on the LTE network optimization capacity for data access fulfillment in Makassar. This research was conducted from October 2015 until January 2016. The location of the research was conducted in one of telecommunication provider service provider company in Makassar, Telkomsel Tbk, which inaugurated LTE service in Makassar Commercial. As for technical aspect which is needed to determine area coverage is the width of the predetermined area. Makassar city has awidth of 175,77 km2 and comprises of 14 districts. Each cell coverage of the LTE design is 2,33